Visual impairment at baseline is associated with future poor physical functioning among middle-aged women: The Study of Women's Health Across the Nation, Michigan Site. (February 2017) - Chandrasekaran, Navasuja; Harlow, Sioban; Moroi, Sayoko; Musch, David; Peng, Qing; Karvonen-Gutierrez, Carrie
Highlights: The prevalence of visual impairment among mid-life women was high. Mid-life visual impairment predicts poorer physical functioning up to 10 years later. Vision correction may help prevent mid-life functional limitations. Abstract: Objectives: Emerging evidence suggests that the prevalence rates of poor functioning and of disability are increasing among middle-aged individuals. Visual impairment is associated with poor functioning among older adults but little is known about the impact of vision on functioning during midlife. The objective of this study was to assess the impact of visual impairment on future physical functioning among middle-aged women. Study design: In this longitudinal study, the sample consisted of 483 women aged 42 to 56 years, from the Michigan site of the Study of Women's Health Across the Nation. Main outcome measures: At baseline, distance and near vision were measured using a Titmus vision screener. Visual impairment was defined as visual acuity worse than 20/40. Physical functioning was measured up to 10 years later using performance-based measures, including a 40-foot timed walk, timed stair climb and forward reach. Results: Women with impaired distance vision at baseline had 2.81 centimeters less forward reach distance (95% confidence interval (CI): −4.19, −1.42) and 4.26 s longer stair climb time (95% CI: 2.73, 5.79) at follow-up than women without impaired distance vision. Women with impaired near vision also had less forward reach distance (2.26 centimeters, 95% CI: −3.30, −1.21) than those without impaired near vision. Conclusion: Among middle-aged women, visual impairment is a marker of poor physical functioning. Routine eye testing and vision correction may help improve physical functioning among midlife individuals.